Smart Campus e Analytics para redução da evasão e promoção da permanência no ensino superior: um estudo de caso múltiplo - Schenatz, Biancca Nardelli (2019)
This thesis aims to explain how the development of a Smart Campus dimensions and the use of Analytics can contribute to the reduction of dropout and the promotion of student permanence in Higher Education. The problem of dropout in higher education institutions has been debated since the 1960s, but since then universities have undergone major transformations in teaching-learning processes, especially with the insertion of technologies in formal and informal educational spaces. Initiatives to make campuses more intelligent have already been used by several institutions of higher education around the world, with the aim of offering improvements in all aspects related to university life. Like a smart city, a university campus has dimensions that can lead a student to want to stay in the educational institution, depending on the experiences they experience during their graduation. In addition to the Education aspect, the main reason for the existence of a campus, there are aspects directly related to students, such as the Social, Health and Safety aspects, and aspects that make campuses more sustainable, such as Buildings, Energy, Mobility and Natural Resources. The Management aspect is fundamental for the promotion of permanence, besides Technology, which integrates all other aspects. The use of emerging technologies such as Analytics by higher education institutions provides its managers with favorable conditions for the decision-making process, the promotion of permanence and institutional experiences that integrate the academic community. This study is based on the Student Integration Theory developed by Vincent Tinto, whose model discusses the ideal settings of a higher education institution to avoid dropout. The present research advances in this issue, proposing a new theoretical model with the extension of the Tinto’s model to a Smart Campus context, in which the data analysis (Analytics) is configured as a powerful tool to support the managers to understand the profile of their students, their needs and the promotion of permanence.